2016
DOI: 10.1016/j.diagmicrobio.2016.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two chromogenic media for the detection of vancomycin-resistant enterococcal carriage by nursing home residents

Abstract: We compared ChromID VRE and Brilliance VRE media for the detection of vancomycin-resistant enterococci (VRE). Using a panel of 28 enterococcal isolates, 10 vanA Enterococcus faecium and three vanA Enterococcus faecalis isolates grew as per manufacturers’ instructions whilst growth of two vanC and eight vancomycin-susceptible enterococci was inhibited on both media. Important differences were noted in the selectivity and chromogenic properties of the two media for vanA Enterococcus raffinosus and vanB E. faeciu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
(31 reference statements)
0
3
1
Order By: Relevance
“…Regarding sensitivity, similar results have been obtained in previous studies evaluating the performance of chromID™ VRE. 1 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 In relation to the specificity, previous studies have obtained values higher than 95%, 1 , 7 , 8 , 11 in contrast to the low specificity observed in this study.…”
contrasting
confidence: 88%
“…Regarding sensitivity, similar results have been obtained in previous studies evaluating the performance of chromID™ VRE. 1 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 In relation to the specificity, previous studies have obtained values higher than 95%, 1 , 7 , 8 , 11 in contrast to the low specificity observed in this study.…”
contrasting
confidence: 88%
“…Although they are less sensitive, culture-based methods may more closely reflect a patient’s ability to transmit VRE, as positive cultures correlate with higher density of stool and in turn with skin colonization 28 . It is expected that ICU patients would have a high load of VRE carriage, 29 and cultures were incubated for 48 hours, which increases the sensitivity of VRE detection 30 . It is therefore likely that most VRE carriers in the ICU were identified.…”
Section: Discussionmentioning
confidence: 99%
“…Also, we relied on direct plating to solid VREfm screening agar for inclusion in our study. Previous studies have shown a sensitivity of 58-96% for this approach, rising to 97-100% with a pre-enrichment step (4547). In our study, P49 carried ST1424, ST80, and ST789 on their first positive screen having been negative for VREfm 11 days previously, suggesting either infection with a mixed population from another host not detected by our sampling strategy or an initial false negative VREfm screen.…”
Section: Discussionmentioning
confidence: 85%